Forensic DNA evidence interpretation - Buckleton, John S.; Bright, Jo-Anne; Taylor, Duncan (CRC Press, Taylor & Francis Group, 2016)
It provides students and professionals with a scientific grounding in biological evidence-both the techniques used to identify it and the methodology to analyze it.